Chemical Characteristics of Non-Gluten Cookies (Study of the Proportion of Mocaf Flour and Edamame Flour with the Addition of Margarine) as an Alternative to Snacks for Celiac Sufferers - Nur Azizah Alifia Rachman; Ratna Yulistiani; Dedin Finatsiyatull Rosida (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2026)
Cookies are a type of biscuit made from soft dough and have a crispy texture when broken. Non-gluten cookies made from mocaf flour and edamame flour have the potential to be an alternative snack for celiac sufferers, while the addition of margarine plays a role in improving the quality and texture of the product.  The purpose of this study was to determine the effect of the proportion of mocaf flour and edamame flour as well as the addition of margarine on the physical, chemical, and organoleptic characteristics of non-gluten cookies, and to determine the best treatment. The study used a Completely Randomized Design (CRD) factorial pattern with 2 factors and 2 replications. The first factor is the proportion of mocaf flour and edamame which (50%:50%, 60%:40%, 70%:30%). The second factor is the addition of margarine (45%, 55%, 65%). The data was analyzed using Analysis of Variance (ANOVA) and continued with the Duncan test at the 5% level. The results showed that there was a real interaction between the treatment of the proportions of mocaf flour and edamame flour and the addition of margarine to the chemical and physical characteristics of non-gluten cookies. The best treatment was obtained in the proportion of mocaf flour and edamame flour (60%:40%) with the addition of margarine 55% recommended with the criteria of moisture content 4.6%, ash content 1.58%, protein content 10.57%, fat content 27.69%, carbohydrate content 55.56%, fracture strength 845 gf and organoleptic test color 4.2; aroma 3.8; taste 4.16 and texture 4.00 Contribution to Sustainable Development Goals (SDGs):SDG 2: Zero Hunger SDG 3: Good Health and Well-being SDG 12: Responsible Consumption and Production